Preliminary Studies on the Content of Phytochemical Compounds On Skin of Salak Fruit (Salacca zalacca) - Setyawaty, Rety (Pharmaceutical Journal of Indonesia, 2020)
Salak fruit plants (Salacca zalacca) are native to Indonesia. Some Indonesian people use this Salak fruit plant as traditional medicine. This plant belongs to the Palmae family. The purpose of this study is to determine the content of phytochemical compounds in the skin of Salak fruits (Salacca zalacca).               The method to get thick extract used extraction-maceration method with 96% ethanol solvent and analyzed by a series of phytochemical tests and using a thin layer chromatography method. In the drying process used 1 kg of fresh skin Salak fruit (Salacca zalacca) and produces 625 g of dried. We are called simplisia. The extraction-maceration process uses 100 grams of simplisia. The simplisia is soaked using 96% ethanol for 3 days and filtrated until thick extract is obtained. The thick extract obtained was 10.69 g with a yield of 10.69%. The thick extract is analyzed alkaloids, steroids, triterpenoids, saponins, tannins and flavonoids by using chemical reaction and thin layer of chromatography. The mobile phase used is toluene: ethyl acetate in a ratio of 9.3: 0.7. The stationary phase used silica gel GF 254.     Based on the phytochemical analysis, the skin of Salak fruits (Salacca zalacca) contains alkaloids, triterpenoids, saponins, tannins, and flavonoids. In addition, based on analysis using Thin Layer of Chromatography produced Rf 0.1875 and is thought to contain terpene alcohol.  Therefore, it can be concluded that the skin of Salak fruits (Salacca zalacca) contains alkaloids, triterpenoids, saponins, tannins, and flavonoids. While observations using Thin Layer Chromatography with mobile phase toluent : ethyl acetate (9.3: 0.7) under UV light of 254 nm and 366 nm is obtained Rf 0.1875 and suspected as terpene alcohol.